Building Your Company's Capabilities Through Global Expansion - Vives, Luis; Lucea, Rafael; Lessard, Donald (MIT Sloan Management Review, 2013)
New markets and new possibilities for expansion and acquisition make the global competitive landscape more dynamic, creating both threats and opportunities. The task of the global strategist involves not only identifying where to leverage a company's existing strengths but also how to enhance and renew its capabilities. The authors argue that the risks of global expansion can be greatly reduced by taking a systematic approach to the decision-making process about entering a new country. They conclude that the experience of many global companies suggests that expensive mistakes are often made when companies don't ask certain key questions before they make such internationalization decisions. By better understanding the nature of their own competitive advantages and how those advantages might fit into or be augmented by a new market, companies can greatly improve their chances of success. The authors illustrate their argument by drawing on the examples of companies such as CEMEX, Telefónica, Accor, Wal-Mart and IKEA. The authors propose two tests for the global strategist, one to use when a company is considering replicating a successful strategy in a new country, and the other to use when a company is seeking to acquire a new capability in a new market.